Executive privilege - Margolin, Phillip (New York, NY : Harper, 2008)
When private detective Dana Cutler is hired by an attorney with powerful political connections, the assignment seems simple enough: follow a pretty college student named Charlotte Walsh and report on where she goes and whom she sees. But then the unexpected happens. One night, Cutler follows Walsh to a secret meeting with Christopher Farrington, the president of the United States. The following morning, Walsh's dead body shows up and Cutler has to run for her life. In Oregon, Brad Miller, a junior associate in a huge law firm is working on the appeal of a convicted serial killer. Clarence Little, now on death row, claims he was framed for the murder of a teenager who, at the time of her death, worked for the then governor, Christopher Farrington. Suddenly, a small-time private eye and a fledgling lawyer find themselves in possession of evidence that suggests that someone in the White House is a murderer. Their only problem? Staying alive long enough to prove it.--From publisher description.
Keywords: Private investigators -- Washington (D.C.); Murder -- Investigation; Women college students -- Crimes against; Political crimes and offenses; Washington (D.C.); Political fiction; Mystery fiction